Peaceful coexistence: lessons from Andamans - Kailash (2000)
The centrally administered Andaman islands with their unique history, ethnic composition, geographical restrictions have developed a secular, progressive and egalitarian society. The article profiles the population and discusses causes for the island's ethnic harmony. - Reproduced
Keywords: Social class